PENGARUH DESAIN PESAN DUA SISI PADA VIDEO TERHADAP PENGETAHUAN DAN PENILAIAN PETANI PADA GOOD AGRICULTURAL PRACTICES (GAP) BAWANG MERAH DI BANTEN - Vina Mahdalena; Pudji Muljono; Cahyono Tri Wibowo (Universitas Muhammadiyah Jakarta, 2018)
The structure of the message has an important role in communication persuasion that can change farmer’s knowledge and their perceived attributes of innovations about Good Agricultural Practices (GAP) of shallot in Banten. Two-sided message design is effective in changing and strengthening one’s attitude according to the purpose of the message content because it has a balanced information between the advantages (positive) and the weaknesses (negative). The purpose of study is to analyze the two-sided message can improve farmer’s knowledge and change their perceived attributes of innovations about GAP of shallot. The method used is experimental model Solomon four-group design because of the highest accuracy. This study was conducted in Gempol Sari Village involving 48 farmers divided into four groups observation. The results showed that there was no interaction between treatment and pretest, it can be ascertain that the changed by treatment. Furthermore, the design of a two-sided message in farmer video has proven to be effective improving their knowledge but has not been proven to change perceived of innovations. This is because farmer’s perceived on the innovations pretest already in the favorable category, so that when given the treatment, their perceived still remain in that category. The conclusion of the study shows that two-sided message video can improve farmer’s knowledge, while the pretest of perceived that originally was in the favorable category reach more higher score on posttest because of the treatment effect. Keywords: GAP, knowledge, perceived attributes of innovations, solomon design, two-sided message